Experimental study on the effectiveness of sterilizing pouch, bond paper, dental bib and cheesecloth in instrument box in preventing contamination of mouth mirrors within a 24-hour period - Guzman, Ernest Joie T.
Sterilization involves use of different packaging systems to ensure prolonged sterility of instruments. These include materials such as dental bib, cheesecloth, bond paper, and sterilizing pouches. The research attempts to identify which of these packaging systems prevents recontamination after sterilization within a 24 hour storage period.